The relationship between depression, stress, anxiety, and postpartum weight retention: A systematic review - Shahin Bazzazian; Hedyeh Riazi; Mohammadreza Vafa; Zohreh Mahmoodi; Malihe Nasiri; Tahereh Mokhtaryan-Gilani; Giti Ozgoli (Wolters Kluwer Medknow Publications, 2021)
Postpartum weight retention (PPWR) is a factor that causes permanent obesity and subsequent chronic and noncommunicable diseases. The relationship between depression/stress/anxiety and PPWR has been studied in some articles, but there is no definitive conclusion in this regard. The present systematic review was conducted to investigate the relationship between depression/stress/anxiety and PPWR. An extensive search was performed in the PubMed, Scopus, Embase, Web of Science, Google Scholar, SID, and Magiran, Irandoc databases using Medical Subject Headings terms (or their Persian synonyms) from 2000 to 2020. Inclusion and exclusion criteria were used for articles selection. The quality of the selected articles was assessed using the Newcastle-Ottawa Scale. Out of 371 reviewed articles, 24 articles were selected. The total sample size was 51,613 (range: 49-37,127). The mean of PPWR ranged from 0.5 kg (standard deviation [SD] = 6.49) to 6.4 kg (SD = 8.5). There was a statistically significant relationship between depression/stress/anxiety and PPWR in 12 of 23, 4 of 6, and 3 of 8 studies. This review demonstrates the relationship between depression/stress/anxiety and PPWR. Time of depression/stress/anxiety assessment is an important issue, as well as different measurement tools. Prevention of the mothers' psychological problems through educational and supportive programs may help to limit PPWR.